2012
DOI: 10.1177/0895904811417587
|View full text |Cite
|
Sign up to set email alerts
|

Charter Management Organizations

Abstract: Policymakers have shown increasing interest in replicating high-quality education models as a way to improve chronically underperforming schools. Charter management organizations (CMOs) have been touted as one organizational model poised to be such a vehicle for reform. CMOs are nonprofit organizations that operate a network of charter schools with a common mission or instructional design and shared central office support. In this article, the authors describe the theory of action behind CMOs and their emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…These examples not only illustrate that school leaders leveraged their own personal connections to wealthy individuals, but also suggest that they invested much time and effort into networking to accrue additional resources. This is in concert with research demonstrating that a common resource mobilization strategy among charter leaders is to engage in direct fundraising (Scott & Holme, 2002), an area where CMOs often have an advantage given their dedicated development and fundraising staff (Farrell, Wohlstetter, & Smith, 2012;Quinn et al, 2016). Among this study's focal schools, Hudson devoted the most human resources to cultivating affluent networks by having on staff a full-time development director, Roseann Street, and a part-time development assistant, Lorrie Fitch.…”
Section: Leveraging the Affluent Network Of Teachers And School Leadersmentioning
confidence: 69%
“…These examples not only illustrate that school leaders leveraged their own personal connections to wealthy individuals, but also suggest that they invested much time and effort into networking to accrue additional resources. This is in concert with research demonstrating that a common resource mobilization strategy among charter leaders is to engage in direct fundraising (Scott & Holme, 2002), an area where CMOs often have an advantage given their dedicated development and fundraising staff (Farrell, Wohlstetter, & Smith, 2012;Quinn et al, 2016). Among this study's focal schools, Hudson devoted the most human resources to cultivating affluent networks by having on staff a full-time development director, Roseann Street, and a part-time development assistant, Lorrie Fitch.…”
Section: Leveraging the Affluent Network Of Teachers And School Leadersmentioning
confidence: 69%
“…The growth of EMOCS has been linked to the desire of policymakers to rapidly expand the number of charter schools in particular states and districts (Scott & DiMartino, 2010). A key characteristic of EMOs, especially larger EMOs, is that they generally provide a replicable educational template that can be readily transferred across neighborhoods, districts, and states (Farrell, Wohlstetter, & Smith, 2012). This provides a quicker route to expansion of charter schools in a given district or state compared to a reliance on grassroots community based groups to open new schools.…”
Section: Background the Growth Of Education Management Organization Omentioning
confidence: 99%
“…This dilemma is becoming increasingly salient in a rapidly evolving charter school landscape. Although by some estimates MOs only represented six percent of all charter schools in 2000 (Miron, 2010), they now represent about one-third of all charter schools (Farrell, Wohlstetter, & Smith, 2012). The tension between the degree of centralized decision-making at CMOs and teacher autonomy that charter practitioners are known to enjoy has potentially significant implications for turnover.…”
Section: Literature Review Teacher Autonomy In Charter Schoolsmentioning
confidence: 99%
“…Using data from 1999-2004, more recent studies found that charter school teachers perceive having more autonomy compared to traditional public school teachers (Ni, 2012;Renzulli, Parrott, & Beattie, 2011). However, Charter Management Organizations (CMOs) or organizations that manage multiple charter schools with a home office offering centralized support have proliferated in the last decade and now account for nearly a third of all charter schools (Farrell, Wohlstetter, & Smith, 2012). CMOs operate networks of charter schools and can be highly prescriptive about school policies and practices (Bulkley, 2005;Lake et al, 2010), causing some to question how CMO teachers perceive and experience autonomy (Scott & DiMartino, 2011).…”
Section: Introductionmentioning
confidence: 99%